Using Of Interpretative Reading To Explain Resistance Mechanisms Of Klebsiella pneumoniae Isolated From U. T. I. Patients - Ibrahim, Jamal Ab-R.; Sharad, Ali A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this study was the isolation and characterization of Klebsiella pneumonia from 160 urine samples of patients hospitalized in children hospital in AL-Ramadi Proveng during October 2006 to May 2008. Also determination of the susceptibility of K. pneumoniae against a number of antibiotics to explain resistance mechanism for these antibiotics by using interpretative reading to avoid using it in treatment. Forty two isolates were detected as K. pneumoniae with resistance to a number of antibiotics . These isolates were tested to determine their sensitivities to a wide number of antibiotics which included β-lactum group and aminoglicosides using disk diffusion method and the strain E. coli ATCC 25922, using as standard strain. The interpretative reading of the sensitivity data to β-lactamas inferred the following: Classical type of K. pneumoniae 7\42 (16,6%), penicillinase-high level producing 6\42(14.2), 29\42(68.9%)ESBLs enzyme producing isolates. Then 7\42(16.6) producing ESBLs- Ceftazidimase enzyme and 22\42 (52.3%) ) producing ESBLs- Broad enzyme. As for aminoglicosides the interpretative reading inferred the following : Classical type of K. pneumoniae 4\42 (9.5%) and 8\42 (19%) producing enzymes AAC(3´)-I,11\42(26%) producing enzymes AAC(3´)-I I,6\42(14%) APH(3) enzymes and 5\42 (11,9%) AAC(6´)-II enzyme further, the enzymes ANT(3) were 8\42 (19%). The results of the present study indicated that K. pneumoniae strains had unusual resistance protocols and this high percentage of strains that produce β-lactamas enzymes in K. pneumoniae referred to wide unusual uses of antibiotics and poor control on infection in hospital.